Critical success factors towards knowledge sharing in Tenaga Nasional Berhad (TNB) Kota Bharu / Fatimah Az-Zahra Wahid - Wahid, Fatimah Az-Zahra (2016)
As we know, workers are important for all the organizations around the world because they are valuable asset for the company. Thus, the companies need to provide a good facilities and tools to make easier for the staff to share their knowledge. The research has been undertaken to determine the factors influencing the knowledge sharing at Tenaga Nasional Berhad in Kota Bharu. The objectives of this research are to determine the dominant factor that contributes to knowledge sharing and to determine significant relationship between trust, communication, information system/technology, reward system and organization structure with the knowledge sharing. The study done by using the primary data as sources. The target of population is the staff of TNB Kota Bharu with 150 respondents by using questionnaires and 132 of the questionnaires is usable for this study. The data will be analyzed by using SPSS Software and this study focused on frequency analysis, descriptive analysis, reliability analysis, Pearson correlation analysis, multiple regression analysis of data and hypotheses testing. The results shows positive relationship between all the five independent variables including trust, communication, information system/technology, reward system and organization structure with the knowledge sharing among TNB Kota Bharu's staffs. In conclusion, majority of staffs in Tenaga Nasional Berhad (TNB) Kota Bharu were transfer and share the knowledge among their colleagues in the company.